Analisis Kesulitan Manajemen Waktu Mahasiswa Semester 6 dalam Menghadapi Tuntutan Akademik dan Kegiatan Lapangan - Dwi Putri Lestari; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study is motivated by the high academic demands faced by sixth-semester students, such as assignments, examinations, reports, proposal seminars, and preparation for field activities such as internships and Kuliah Kerja Nyata. The many responsibilities that must be carried out simultaneously cause some students to experience difficulties in managing their time effectively. The purpose of this study is to analyze the time management difficulties of sixth-semester students in dealing with academic demands and field activities. The method used is descriptive qualitative research with a case study approach. Data were collected through observation, interviews, and documentation involving sixth-semester students selected purposively, then analyzed using the interactive model of Matthew B. Miles and A. Michael Huberman which includes data reduction, data display, and conclusion drawing. The findings indicate that students experience difficulties in determining task priorities, procrastination habits, fatigue due to dense schedules, lack of discipline in following plans, and pressure caused by overlapping academic and field activity schedules. Supporting factors for successful time management include self-discipline, social support, and the use of daily schedules. Therefore, students need to improve their time management skills in order to balance academic responsibilities and field activities optimally.